Understanding The Experience of Pesantren Alumni in Adaptation With Environment Beyond Pesantren. - Nur Sholekhatun Nisa; Dra. Taufik Suprihartini, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The background of this research is the experience of pesantren (Islamic boarding school) alumni in adapting with the external environment of pesantren. The pesantren alumni who have graduated from pesantren move into new environment outside the pesantren, so that they adapt to their new environment. This research aims to describe the pesantren alumni’s experience in adapting with the new environment after they graduate from pesantren. This research uses the Anxiety and Uncertainty Management Theory (Gudykunst, 1995), Uncertainty Reduction Theory (Leanne K. Knobloch, 2008), Expectancy Violations Theory (Cindy H. White, 2001), Theory of Motivated Information Management (Afifi and Weiner, 2004), and Interactions Adaptation Theory (Burgoon, 1995). Qualitative research approach is applied, referring to interpretive paradigm. The data analysis technical is based on phenomenology research. The informants of this research are 4 pesantren alumni. The results of this research find that there are 3 main points. First, each informant has different level of anxiety and uncertainty as the initial behavior in moving process. The first, third, and fourth informant experience higher anxiety and uncertainty than the second informant. The anxiety and uncertainty caused by the lack of information of new environment. Second, information is the important factor which helps the adaptation process. All informants use 3 adaptation strategies; active, passive, and interactive strategy. Those strategies are used to obtain kinds of information. Third, the success of adaptation process in the new environment determines the decision making whether the informants bring pesantren values and culture. The results show all informants successfully adapt into their new environment outside pesantren, and their level of anxiety and uncertainty decrease. The first and second informants decide to bring pesantren values and culture to their new environment. Meanwhile, the third